The Direct and Indirect effect of Employee Empowerment and Employee Engagement on Innovative Work Behaviour within Manufacturing Sector in Kenya - Kanake , Mercy K.; Kemboi , Ambrose; Tenai , Joel (African Journal of Education,Science and Technology (AJEST), 2020)
This research aimed at developing and testing a conceptual model that explores the relationship between employee empowerment, employee engagement and innovative work behaviour (IWB). The framework for this study was drawn using the Social Exchange Theory (SET) based explanatory research design. This research investigated the impact of employee engagement on the relationship between employee empowerment and employees' innovative work behaviour. The study examined the direct and indirect mechanism of employee empowerment and creative work behaviour through the mediating impact of employee engagement, which helps achieve the desired goals of the organization. The data were collected through a self-administered questionnaire from 470 respondents in the manufacturing sector located within Nairobi City, County, Kenya. Research was carried out using Hayes PROCESS Macro model 4. The findings confirmed that employee empowerment had a positive significant effect on employee engagement; employee engagement had a positive significance on IWB; employee empowerment was found to have a positive significant effect on IWB. Further, the results revealed a partial mediation effect of employee engagement on the relationship between employee empowerment and innovative work behaviour. In conclusion, the direct influence of employee empowerment on innovative behaviour among employees can be improved through their engagement. The study recommends that employee empowerment and engagement practices be considered and implemented by organizations in order to enhance employees’ innovative behaviour.